Combined use of 2D electrical resistivity and seismic refraction in hydrogeophysical exploration - Musa, A.A. (Slovnaft VURUP a.s, 2017)
The knowledge of the geometry and the physical properties characterizing the subsurface has been a challenge for groundwater exploitation. The relationship between lithological properties, electrical distribution and wave velocity was explored for this research as a means of detecting porous aquifers. The geophysical exploration involved electrical resistivity and seismic refraction surveys in parts of Selangor and Pahang areas of Malaysia. 2D resistivity conducted in these areas generated profiles from which probable positions of groundwater were identified. The field acquired resistivity data were processed with the use of RES2DINV software. For the seismic refraction method, magnitudes of wave velocity values were used to estimate depths to aquifer zones and to map the bedrock surface and subsurface structures. The high resolution seismic data that was gathered was processed and interpreted with the GREMIX program. A good hydrogeological interpretation was possible by constraining the geoelectric inversion and seismic velocities using information from known geology of the study areas. Both methods were effectively combined to ascertain the presence of fracture aquifer in hardrock complexes. Good correlation between electrical resistivity and seismic survey results confirmed the usage of integrated geophysical techniques as a reliable tool in providing useful information of the subsurface.